Problem Based Learning Model Assisted by Wordwalls: Learning Motivation at Elementary School Students' - Khairunnisa, Fadhilah; Ifrianti, Syofnidah; Erfayliana, Yudesta (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Due to a lack of student motivation, various learning approaches, and engaging learning media, classroom learning has not featured student interaction. Therefore, the purpose of this study is to determine whether the Problem-Based Learning (PBL) model assisted by Wordwall has a significant influence on elementary school students' learning motivation. This quantitative research employs a quasi-experimental that utilizes a pretest-posttest control group design. This research was conducted on grade V students of State Elementary Madrasah 1 Bandar Lampung. Data collection techniques include distributing a list of questions to respondents or survey questionnaires. Descriptive data analysis is used to measure and present initial (pre-test) and final (post-test) data using the paired t-test. The study found t = -4.577 for the experimental class paired samples t-test. In the experimental class, a significant value of 0.000 < 0.05 was found. The Problem-Based Learning (PBL) model, supported by Wordwall, significantly impacts class V students' learning motivation, with a sig. value of 0.000 < 0.05, rejecting H0 and accepting H1. The paired samples t-test showed a value of t = 0.487 with a significance of 0.630 > 0.05, indicating that H0 is accepted and H1 is rejected. The Teams Games Tournament (TGT) model assisted by a PowerPoint presentation did not affect class V students' learning motivation. Therefore, the Problem-Based Learning (PBL) model supplemented by Wordwall affects class V students' learning motivation at State Elementary Madrasah 1 Bandar Lampung.